Community booklet on certified seeds for beans - Lengewa, C.; Mikhala, Audrine; Aura, S.; Amuda, A.; Yila, Jummai; Bomuhangi, Allan; Nchanji, Eileen (2024)
Beans are the edible seeds of various plants in the Fabaceae family, commonly known as legumes. Beans are an important food in our country and many parts of the world. Today in this booklet, let us briefly discuss the benefits of certified seeds for beans, including the opportunities in agri-business for farmers, women and youth.